The Zooplanktonic Communities of Cârja And Mălina Farms (Romania) - Daniela Cristina IBĂNESCU; Adina POPESCU; Ion VASILEAN (ACROSS)
Zooplankton communities represent an important link in the aquatic food web with an important role in the transmission of matter and energy from producers to consumers. Also, they are excellent indicators of water quality and their functioning through their central position in the food web. This study presents the taxonomic composition, abundance, and spatio-temporal distribution of zooplankton communities in two pond ecosystems with different water supply sources, in two seasons (spring and autumn). Diversity and similarity for the three zooplankton groups between the two fish farms were also calculated. The study was conducted in 2020.